Le dialogue philosophique perçu par les personnes qui le pratiquent ou le promeuvent : une activité anthropologique utilisée pour former au penser ensemble face aux défis actuels. - Claire Polo; Justine Broussais (Éducation et Socialisation)
Based on a French corpus of 12 semi-structured interviews with people practising philosophical dialogue with 'lay people' (children, prisoners, families, people attending a show), we investigate the meaning given to this activity. While there is a relative consensus among all the stakeholder on a general positive stance attributed to philosophical dialogues, without formulating specific expectations about it; diverse ideas are mentioned when they are prompted to explain such positive contribution. We describe them by distinguishing between two poles structuring the conceptions of the interviewees: philosophical dialogue as 1. a timeless anthropological reality which insufficient in itself, and as 2. a utilitarian response to the specific challenges currently undermining our societies. We therefore review the expected and perceived benefits for a) the participants invited to engage in dialogue, b) the people leading these exchanges and/or c) the institutions making this activity possible. The aim is to present the constructive/fruitful or detrimental tensions resulting by the joint reference to both pol: philosophical dialogue as an anthropological reality and a utilitarian response.